RELATIONSHIP OF INTERNAL AUDITOR INDEPENDENCE, INTERNAL AUDIT EFFECTIVENESS AND SHARIA COMPLIANCE (CASE STUDY ON SHARIA BANK IN EAST JAVA) - Yulisnawati, Yulisnawati; Pramono, Sigit Eko; Laela, Sugiyarti Fatma (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2023)
This study aims to analyze the impact of the effectiveness of internal audit in improving sharia compliance in this case effectiveness is highly dependent on the independence of internal auditors. The subjects of this research are all internal auditors who work for Islamic banks in East Java province. The sample used in this study was taken through purposive sampling method. This study uses a type of quantitative research with hypothesis testing. In this study using Partial Square Structural Equation Modeling (PLS-SEM) analysis used for validity tests and reliability tests with the help of analytical tools in the form of Smart-PLS 4.0 software. The results of this study indicate that the internal auditor independence variable has no significant effect on sharia compliance. The internal audit effectiveness variable has a significant effect on sharia compliance. The internal auditor independence variable has a significant influence on the effectiveness of the internal audit. And the internal auditor independence variable has a positive effect on Sharia compliance by means of internal audit effectiveness.